Relationship between nursing work environment and clinical decision-making among Saudi nurses: psychological empowerment as mediator - Abdulhafith Alharbi; Sameer A. Alkubati; Hamdan Albaqawi; Aziza Z. Ali; Laila A. Hamed; Shaimaa Mohammed; Larry Terence O. Cornejo; Eddieson Pasay-an (BMC Nursing)
Abstract Background Clinical decision-making in the context of nursing practice is considered an essential skill for nursing practitioners. Nonetheless, various factors, such as the work environment and nurses’ psychological empowerment (PE), may negatively influence their decision-making ability. Therefore, this study assessed the relationship between clinical decision-making (CDM) and the nursing work environment (NWE), focusing on the mediating role of PE among clinical nurses in Hail Province, Saudi Arabia. Methods This cross-sectional study used a self-administered questionnaire to collect data from 298 nurses at five hospitals in Hail Province, Saudi Arabia, from January to March 2025. Besides demographic characteristics, the questionnaire included the following tools: the CDM, the NWE-questionnaire, and the PE Scale. Multiple linear regression was used to identify significant predictors of both CDM and PE. The mediating role of PE on the relationship between NWE and CDM was examined using Hayes’ Process Macro program v4.2 (Model 4). Results Multiple linear regression revealed that being a head nurse and perceiving a more positive NWE were significant predictors of higher scores of nurses’ PE (P < 0.05). On the other hand, being a registered or head nurse, working more than five days per week, and perceiving a more supportive NWE were significant predictors of higher levels of nurses’ CDM (P < 0.05). Conversely, working regular night shifts was a significant predictor of lower scores of nurses’ CDM. A significant positive direct effect and total effect were found between NWE and nurses’ CDM (B = 0.136, P = 0.017 and B = 0.273, P < 0.001, respectively). The indirect effect (B = 0.137), based on 5,000 bootstrap resamples, had a bootstrap confidence interval above zero (0.021 to 0.263), indicating a partial positive mediating role of PE in the relationship between NWE and CDM. Conclusion PE plays a vital role in fostering CDM and promoting a supportive NWE for nurses in clinical settings across Hail Province. These insights emphasize the need for establishing psychologically empowering conditions in the workplace to level up nurses’ self-perceived competence and confidence in CDM. Clinical trial number Not applicable.